Crash reduction factors for traffic engineering and intelligent transportation system (ITS improvements) state-of knowledge report. - Harkey, David L.; National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program (Washington, D.C. Transportation Research Board, 2005)
"This digest is an interim deliverable from NCHRP Project 17-25, 'Crash reduction factors for traffic engineering and ITS improvements,' which is being carried out under a contract with The University of North Carolina Highway Safety Research Center (HSRC) under the direction of David L. Harkey (Principal Investigator)."--P. [1].
Caption title.
At head of title: National Cooperative Highway Research Program.
"November 2005".
Includes bibliographical references (p. 27-31)
Also available online via the TRB website.
Keywords: Roads -- Safety measures; Traffic safety; Intelligent transportation systems